Evaluación del efecto en la adición en la dieta para cerdos en la etapa de crecimiento y engorde de diferentes porcentajes de yogurt de yuca - Diaz Jame, Katryn Sullyn (2023)
Pig farming in Ecuador has had a great impact on the agricultural sector, it is determined as one of the main actions that are established for economic performance. In this work, the benefits offered by the addition of cassava yogurt in different percentages present in pigs that correspond to the growth and fattening stage were evaluated, by supplying it, the feed conversion, feed consumption, carcass yield will be determined. , feed conversion and weight gain obtained weekly by weighing them. A diet supplemented with by-products obtained from cassava has been determined as possible viable forms of production and fattening of piglets. The addition of cassava yogurt was evaluated in different percentages (10 and 20%), in which favorable results were presented in the different aspects that were considered at the time of the evaluation. Statistically, there was no significant difference between the weights of the respective treatments, however, according to what was stated in the different tables, the weight difference between the cassava yogurt addition treatments was established in contrast to the control treatment that presented a weight of less than of the data obtained through the biased evaluation. Thus, it is also established that the piglets added with 20% cassava yogurt presented higher performance, followed by the treatment established at 10% cassava yogurt, which presented similar weights, while the control treatment presented lower performance.